Diversification of Processing of Cock Fish Bone Chips (Channa striata) with Different Compositions - Fuji Astuti; Fitra Mulia Jaya; Lia Perwita Sari (Faculty of Fisheries and Marine, Universitas Riau, 2022)
Processed fishery products produce unwanted materials, namely waste. Waste is generated in the form of heads, tails, fins, bones, and offal. Bone is one form of waste generated from the fish processing industry which has the highest calcium content in the fish body. Snakehead fish bone waste (Channa striata) is one of the potential food ingredients that is widely used in South Sumatra, especially in the city of Palembang as a raw material for processed Palembang specialties. Diversification of processed fishery products needs to be developed. In this study, the authors innovate processed products made from cork fish bones to increase the nutritional value of the community through protein and fish calcium in the form of processed products of cork fish bones chips. This research was conducted from April to June 2021. This study aims to determine the effect of using the addition of cork fish bones in the manufacture of fishbone chips with different compositions and to obtain the best chip products from the use of s cork fish bones. The method used was an experiment using a Completely Randomized Design (CRD), with 4 levels of treatment P0:0% (Without the addition of cork fish bones and 300 g of Wheat Flour) P1:20% (60 g Addition of cork fish bone and 240 g of Wheat Flour). ) P2: 25% (75 g cork fish bone and 225 g Wheat Flour), P3: 35% (105 g cork fish bone and 195 g Wheat Flour). The parameters measured in this study were organoleptic tests (appearance, aroma, taste, and texture) and proximate tests (moisture content, protein content, fat content, ash content, and carbohydrate content). The results showed that the best treatment on the P3 chips treatment: 35% (105 g Addition of Cork Fish Bone and 195 g Wheat Flour) including the best organoleptic average values ​​obtained in color (58.0) Aroma (60) Taste (52.5), and Texture (59.5). Chips P3: 35% (Addition of Cork Fish Bone 105g and Wheat Flour 195g) including proximate test, average water content is 3.09%, protein content is 18.68%, fat content is 28.81%, ash content is 6.30 %, and carbohydrate content is 43.12%.